Functional Donor Site Morbidity After Vascularized Toe Transfer Procedures: A Review of the Literature and Biomechanical Consideration for Surgical Site Selection. Issue 6 (June 2016) - Sosin, Michael; Lin, Cheng-Hung; Steinberg, John; Hammond, Edward R.; Poysophon, Poysophon; Iorio, Matthew L.; Patel, Ketan M.
Abstract : Background: The purpose of this study was to conduct a systematic review and pooled analysis of vascularized toe-to-hand transfer to determine functional donor site morbidity among different techniques. Methods: Pubmed MEDLINE, EMBASE, and Cochrane databases search yielded 302 citations, with 56 meeting inclusion criteria. Pooled outcomes and analysis are reported based on donor site morbidity, specific toe transferred, technique used, and foot biomechanical changes. Results: A total of 802 digit transfers (418 isolated great toe transfers, 324 isolated second toe transfers, and 153 toes classified as "other") were included for analysis. Sex was reported in 510 patients (80.2 % men, 19.8% women). The mean patient age was 28.5 ± 8.4 years. Functional impairment analysis found 23.7% (97 digit transfers) experienced gait impairment. Great toe transfer versus second toe transfer versus the "other" group demonstrated morbidity rates of 21.8%, 14.5%, and 23% ( P = 0.001), respectively. Donor site reoperative intervention occurred in 11.8% of cases (95 digits): 4.5%, 16.6%, and 16.0% ( P < 0.001), respectively. Mean follow-up time was 62.6 months. Conclusions: Functional foot impairment can occur after various toe transfer procedures due to altered biomechanics of weight distribution and gait. Rigorous biomechanical foot evaluation of this subset of patients is lacking. Great toe transfer appears to have the highest morbidity rate, but lower reoperative intervention as compared to second toe transfer. Preserving ray projection does not prevent biomechanical changes to the foot, but may delay functional impairment leading to favorable functional interpretation by patients and surgeons.